On sea and land, on creek and river being an account of experiences in the visitation of assemblies of Christians in the West Indies and British Guiana; with reminiscences of pioneer missionaries and of the slave trade formally carried on from Bristol - Case, Henry W. (London, UK Morgan and Scott, 1910)
Includes photographs.
Brethren writer.
Keywords: Brethren movement -- missions -- West Indies